Validation of Acceleration Response Modelling for Modular High Rise Structures through Full Scale Monitoring - Fitzgerald, Breiffni; Broderick, Brian; Hickey, John (My University, 2023)
For many tall building forms, habitability requirements associated with excessive acceleration response become a governing design criterion as building heights increase. The application of modular construction methods to high-rise construction is a relatively new concept with limited previous research being conducted on the dynamic properties of tall modular buildings. Further to this, the real contribution of individual modular elements to overall lateral stiffness is largely unknown leading to significant uncertainty in acceleration response predictions. As modular construction continues to be employed in structures of ever-increasing height, the susceptibility of this form of construction to wind induced accelerations requires further investigation. This research considers the comparison and validation of computational models of a tall volumetric corner post modular structure with an RC core. Both Finite Element Models (FEMs) and mathematically-equivalent mechanical models adapting an analytical stepped beam approach are developed and the inherent properties such as the natural frequencies and mode shapes are calculated. The inherent properties predicted by the models are compared to those obtained from the actual measured response as captured through a full-scale monitoring campaign. A full-scale monitoring campaign employing two triaxial accelerometers, a data acquisition system and a data storage system recorded the white noise ambient acceleration response of two tall, slender modular structures with overall heights of 135m and 150m. Wind speed and direction were also recorded throughout the monitoring campaigns. Structural identification techniques were used to process the measured acceleration responses and obtain estimates of the actual natural frequencies and damping ratios of the partially- and fully complete structures. The acceleration response of the structure was captured at varying stages throughout the construction programme as more storeys of modules were added to the building and the contribution of the modules to the modal properties evolved. The comparison between the measured inherent properties at the different stages of construction and the model results at the equivalent stage provides vital insight into the overall stiffness contribution of modules in high-rise modular structures. This can lead to more efficient modelling and design procedures for a novel form of building. Furthermore, comparison of the modelled properties and the results from the full-scale monitoring campaign helps to provide a better understanding of model accuracy and identifies opportunities for further refinement of the modelling of tall modular buildings to reduce model size, run time and computational expense, without loss of accuracy in wind-induced response prediction. The validation of the model and identification of stiffness contributions of the modules supports structural optimisation analyses and the numerical investigations required to include vibration response mitigation measures in future designs.
XII International Conference on Structural Dynamics (EURODYN)
PUBLISHED
Delft
Keywords: Smart & Sustainable Planet; Structural Dynamics; Structural Engineering